Biofuel–Pharmaceutical Co-Production in Integrated Biorefineries: Strategies, Challenges, and Sustainability - Tao Liu; Miaoxin He; Rui Shi; Hui Yin; Wen Luo (Fermentation, 2025)
Global demands for sustainable energy and advanced therapeutics necessitate innovative interdisciplinary solutions. Integrated biorefining emerges as a strategic response, enabling the co-production of biofuels and pharmaceutical compounds through biomass valorization. This integrated model holds promise in enhancing resource utilization efficiency while ensuring economic viability. Our critical review methodically evaluates seven pivotal methodologies: seven key strategies: microbial metabolites, synthetic biology platforms, biorefinery waste extraction, nanocatalysts, computer-aided design, extremophiles, and plant secondary metabolites. Through systematic integration of these approaches, we reveal pivotal synergies and potential technological innovations that can propel multi-product biorefinery systems. Persistent challenges, particularly in reconciling complex metabolic flux balancing with regulatory compliance requirements, are analyzed. Nevertheless, advancements in systems biology, next-generation bioprocess engineering, and artificial intelligence-enhanced computational modeling present viable pathways for overcoming these obstacles. This comprehensive analysis substantiates the transformative capacity of integrated biorefining in establishing a circular bioeconomy framework, while underscoring the imperative of transdisciplinary cooperation to address existing technical and policy constraints.